Experimental investigation on flow condensation heat transfer and pressure drop of R170 in a horizontal tube. (June 2016) - Zhuang, X.R.; Gong, M.Q.; Zou, X.; Chen, G.F.; Wu, J.F.
Highlights: Condensation heat transfer and pressure drop of R170 were studied experimentally. The effects of vapor quality, mass flux and saturation pressure were investigated. Predictive models were evaluated for condensation heat transfer and pressure drop. Experimental data are in good agreement with Koyama and Yan-Lin correlations. Abstract: Condensation heat transfer and pressure drop of R170 were studied experimentally in a horizontal tube with inner diameter of 4 mm. The tests were conducted at saturation pressures from 1 MPa to 2.5 MPa, mass fluxes from 100 kg (m 2 ∙s) −1 to 250 kg (m 2 ∙s) −1 and average heat fluxes from 55.3 kW m −2 to 96.3 kW m −2 over the entire vapor quality range. The effects of vapor quality, mass flux and saturation pressure on condensation heat transfer and pressure drop were examined and analyzed. The experimental data were compared with various well-known correlations of condensation heat transfer coefficient and pressure drop. The comparison results showed that Koyama et al. correlation agreed with the experimental heat transfer coefficient with a mean absolute relative deviation less than 25%, and the Yan and Lin correlation can accurately predict the experimental pressure drop with a mean absolute relative deviation less than 18%.